SETTING THE SPEED OF MOTOR AC single phase conveyor Based MICROCONTROLLER - Mandaru, Michael Andriano; Harianto, Harianto; Susanto, Pauladie (Journal of Control and Network Systems (JCONES), 2017)
AC motors are often used for task that require a large torque. One of AC motors application is to drive conveyors that is used to transport material between processes. PID is used to control motor’s speed according to the material’s weight. We use microcontroller ATmega32 to perform PID. As the result, AC motors already have speed that adjusted to given set point with average error 3,6 rpm. Keywords:AC motors, Proportional Integral Derivative (PID), mikrokontroler ATmega32, rotary encoder sensor, conveyors.